From Disinterestedness to Engagement: Towards Relational Leadership In the Cultural Sector - Søren Friis Møller (Copenhagen Business School (CBS), 2012)
The thesis is an inquiry into how leadership is performed narratively in the cultural sector. Chapter 1 draws the cultural sector as a narrative landscape, and the reader is invited on a tour around this narrative landscape as seen through the eyes of some of the top guns in the cultural sector. Seen from this vantage, leadership in the cultural sector seems to be predominantly performed by relating narratives with reference to the metanarrative of the Enlightenment. The inquiry, however, draws on Lyotard (1984) to argue that such extralinguistic legitimization is in a crisis of legitimacy, wherefore the inquiry embarks on a problematization of the dominant understanding of leadership in the cultural sector with the activist aspiration of suggesting a postmoderning understanding of leadership in the cultural sector being performatively legitimized. Chapter 2 argues in favor of a relational, non-entitative understanding of narratives and it points to emplotment as a process of finding the best fit. This relational understanding of narratives allows the project to inquire into leadership performed narratively in all kinds of empirical settings, not confining itself to formal leadership contexts. Chapter 3 offers a genealogic approach to what the project has defined as the dominant narrative in the cultural sector, the narrative of art for art's sake (the AFAS narrative), which the project argues function as an implicit standard. This includes notions of aesthetic autonomy such as suggested by Kant in 1790, artistic freedom and art for its own sake such as claimed by artists in the Romantic era, and the arm's length principle as the `constitution of cultural policies' in the post WW2 Western world. Chapter 4 provides an overview of alternative voices which have challenged the dominant narrative. These include post colonial studies, cultural entrepreneurial studies and consumer behavior studies which in various ways propose alternative ways to lead and support the cultural sector. Chapter 5 links the discussions in chapter 3 and chapter 4 to leadership studies, notably to discussions of leader-centered orientations versus leading relationally orientations. The chapter concludes by suggesting a new sensibility towards understanding leadership and meditates on how this might be achieved, paying attentions to the possibilities of overcoming the putative crisis of legitimacy the inquiry is placed in. Chapter 6 relates a case-study of Malmoe City Library which endeavors into a difficult, yet very promising process of reformulating what a library may become in a contemporary context. This process challenges the dominant narrative and thus the current understanding of what a library should be, and this deviation from the dominant narrative challenges leadership. Chapter 7 assembles three different approaches to challenges the dominant narrative and to make new interpretive resources available to the understanding of leadership in the cultural sector. First, givrum.nu, a social movement working with arts, second, Mogens Holm, a leader in the cultural sector in a transition phase, and third, Copenhagen Phil, a classical symphony orchestra striving to avoid becoming a parallel society phenomenon. These case studies are conducted as written interviews with the cases, in an attempted un-edited form to also introduce relational processes informed by a power with relation to my own research project. Chapter 8 reflects on the case-studies in chapter 6 and chapter 7 in light of the two approaches to leadership discussed in chapter 5. It does so by linking my study to relational leadership theory in order to see how this theoretical field might inform my inquiry and how my inquiry might inform this field. It equally offers five possible reconstructions of the cases before concluding the research project by summing up contributions to the empirical field and the research fields, as well as by pointing to areas which could be further developed in future research. In line with the aspirations of the relational constructionist framework of the project, the inquiry does not offer a conclusion. Instead it encourages further reconstructions, thus submitting itself to the performative legitimization it argues in favor of.
hdl:10398/8590
Keywords: 650